ChemInform Abstract: Copper‐Catalyzed Insertion into Heteroatom—Hydrogen Bonds with Trifluorodiazoalkanes. Issue 28 (June 2016) - Hyde, Stephen; Veliks, Janis; Liegault, Benoit; Grassi, David; Taillefer, Marc; Gouverneur, Veronique
Abstract: Copper‐catalyzed Si—H, B—H, P—H, S—H, and N—H insertion reactions of trifluorodiazoethane and aryltrifluorodiazoethanes generate a large collection of new fluorine‐containing chemical entities for medicinal chemists.